Prevalence and Associated Factors of Stress, Anxiety, and Depression among Parents of Children with Autism Spectrum Disorder - Touheed, Umar; Afzal, Erum; Hassan, Gull; Zafar, Muhammad Salman; Ijaz, Asna; Asghar, Sana (Biological and Clinical Sciences Research Journal, 2025)
Parents of children with autism spectrum disorder (ASD) experience unique psychological challenges due to the chronic nature of the condition, placing them at a higher risk of stress, anxiety, and depression. Understanding these patterns is essential for early mental health interventions and family support programs. Objective: To determine the pattern and burden of stress, anxiety, and depression among parents of children with autism spectrum disorder and their associated factors at a tertiary care hospital. Study Design: Prospective descriptive study. Place and duration of study: The Children's Hospital and Institute of Child Health, Multan, from September 20245 to February 2025. Methodology: Parents of children with autism spectrum disorder (n = 96) were recruited in this study using a non-probability consecutive sampling technique. These study participants were screened for stress, anxiety, and depression using the Depression, Anxiety, and Stress Scale (DASS-21). Results: Of these 96 study participants, 32.3 %(n=31) were male respondents, while 67.7 % (n=65) were female respondents. The mean age of these respondents was 33.70 ± 6.22 years, ranging from 24 to 47 years. The majority of respondents were from urban areas (62.5%), with a middle-income background in 60.4% (n=58), and 56.3% (n=42) were literate. Most of the respondents were homemakers (59.4%; n=57), the joint family system was noted in 69.8% (n=67), and 3.1% (n=3) were divorced. Stress was noted in 61.5 % (n=59), anxiety in 47.9 % (n=46), and depression in 45.8 % (n=44) respondents in our study. Conclusion: A very high burden of stress, anxiety, and depression was noted among parents of children with autism spectrum disorder in our study. Stress was significantly associated with residential status, socioeconomic status, occupation, family system, and literacy. Anxiety was significantly associated with age, residential status, and literacy, while depression was significantly associated with age and marital status.